CsSPL functions as an adaptor between HD‐ZIP III and CsWUS transcription factors regulating anther and ovule development in Cucumis sativus (cucumber). (31st March 2018) - Liu, Xiaofeng; Ning, Kang; Che, Gen; Yan, Shuangshuang; Han, Lijie; Gu, Ran; Li, Zheng; Weng, Yiqun; Zhang, Xiaolan
Summary: Anther and ovule genesis preconditions crop fertilization and fruit production; however, coordinative regulation of anther and ovule development and underlying molecular pathways remain largely elusive. Here, we found that SPOROCYTELESS ( SPL )/ NOZZLE ( NZZ ) expression was nearly abolished in a Cucumis sativus (cucumber) mutant with severely defective anther and ovule development. CsSPL was expressed specifically in the developing anthers and ovules. Knock‐down of CsSPL reduced male and female fertility with malformed pollen and suppressed ovule development. Importantly, CsSPL directly interacted with CsWUS (WUSCHEL) in the nucellus and YABBY family genes in integuments, and positively regulated CsWUS expression, meanwhile the HD‐ZIP III gene CsPHB ( PHABULOSA ), expressed specifically in the nucellus, promoted CsSPL expression by binding to the CsSPL promoter. Thus, CsSPL acts as an adaptor to link CsPHB and CsWUS functioning, underpinning a previously unidentified regulatory pathway orchestrating sex organ development in planta . In addition, auxin accumulation was reduced in the reproductive organs of CsSPL knock‐down plants. Biochemical analyses further showed that CsSPL stimulated the expression of AUXIN RESPONSE FACTOR 3 ( CsARF3 ), and was positively regulated by CsARF13 during reproductive organ development, indicating sequential interactions of CsSPL with auxin signaling components in orchestrating anther and ovule development. Significance Statement: SPL as a vital sporogenesis gene, is essential for anther and ovule development in higher plants, however, its molecular mechanism remain largely elusive. In this study, we uncovered a regulatory pathway in a CsPHB (PHABULOSA)‐CsSPL‐CsWUS (WUSCHEL) manner during ovule development, and found that CsSPL can directly interact with auxin signaling components CsARF3 and CsARF13 during reproductive organ development.